Relationship of Age, Work Period, and Education Level with Occupational Accidents in the South Borneo Coal Industry - Arahnca Sevanya Tanaya1 , Tri Martiana2 , Zikri Fathur Rahman3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Research Background: Occupational health and safety (OHS) is an effort to create a working atmospherethat is safe, comfortable, and the ultimate goal is to create the highest productivity. The higher level ofproduction in the coal industry will be in line with the dangers and risks of work accidents in the coalindustry. Occupational accidents are influenced by 2 (two) direct causes namely unsafe action (unsafe action)and dangerous condition (hazardous condition) Research Methodology: The research design used in thisstudy is observational analytic with the cross-sectional approach with a large sample of 80 respondents whoin the South Borneo coal industry. Data analysis used the statistical test Chi-Square (? = 0.05). Result: Fromthe results of the bivariable significance test using the Chi-Square test showed that the significant value ofage (p= 0.604), years of service (p= 0.544), level of education (p = 0.578) > 0.05. Discussion: There is nosignificant relationship between the variables of age, years of service, education level with work accidentsin the South Borneo coal industry